Development of Career Anxiety Module on Students' Future Orientation - Jeni Astuti Ningrum; Siti Muhibah; Alfiandy Warih Handoyo (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This research was conducted to help college students reduce their level of career anxiety about their future orientation. The researcher tries to offer an alternative solution to this problem by developing a career anxiety module about students' future orientation. In this study using the 4-D development model, which includes several stages, namely define, design, development, and disseminate. The instrument used to measure career anxiety is a questionnaire made by researchers. The data obtained was then analyzed using qualitative and quantitative data analysis, the following results were obtained, 1) the results of the validation test from media, material, and language experts, obtained a percentage value of 96% which means the module is feasible to use because it meets the eligibility criteria for module 2) in the module trial with BK UNTIRTA students class of 2018 getting a percentage score of 98.67%, which means the module is in the proper category. Based on these results it can be concluded that the development of a career anxiety module about student future orientation is acceptable for implementation in society.